2015
DOI: 10.1002/jmor.20380
|View full text |Cite
|
Sign up to set email alerts
|

Development and microstructure of tooth histotypes in the blue shark, Prionace glauca (Carcharhiniformes: Carcharhinidae) and the great white shark, Carcharodon carcharias (Lamniformes: Lamnidae)

Abstract: Elasmobranchs exhibit two distinct arrangements of mineralized tissues in the teeth that are known as orthodont and osteodont histotypes. Traditionally, it has been said that orthodont teeth maintain a pulp cavity throughout tooth development whereas osteodont teeth are filled with osteodentine and lack a pulp cavity when fully developed. We used light microscopy, scanning electron microscopy, and high-resolution micro-computed tomography to compare the structure and development of elasmobranch teeth represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(73 citation statements)
references
References 32 publications
6
66
1
Order By: Relevance
“…Moyer et al (2015) observed in developing teeth of the White Shark that osteodentine filling the inside of the crown is less dense than it is in fully developed teeth owing to the tissue's incomplete mineralization. The lowdensity osteodentine core of USM 9000 suggests that this was a developing tooth rather than a functional tooth.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Moyer et al (2015) observed in developing teeth of the White Shark that osteodentine filling the inside of the crown is less dense than it is in fully developed teeth owing to the tissue's incomplete mineralization. The lowdensity osteodentine core of USM 9000 suggests that this was a developing tooth rather than a functional tooth.…”
Section: Discussionmentioning
confidence: 95%
“…Figure 7 shows 2 intact lower jaw teeth in Porbeagle specimen CUMV 98002 and the location of characteristic lateral cusplets relative to the central cusp. In their earliest stages of development, shark teeth are composed of a hollow crown made only of enameloid (Moyer et al 2015, Peyer 1968). Therefore, a hollow tooth crown might be recovered from an excavation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…To reference other specific teeth in the dentitions of individual specimens, we assigned each tooth an identifying code based on its location in the jaw and its location in its tooth file following the scheme developed by Moyer et al (2015) and Bemis et al (2015). This scheme is similar to that used by Naylor and Marcus (1994) in that it identifies teeth by position along the jaw; however, we also use numbers to denote a tooth's position within a given tooth file.…”
Section: Methodsmentioning
confidence: 99%
“…The teeth on saw blades are formed by removal of excess metal followed by a polishing or honing step. By contrast, shark teeth develop through deposition of material, with the outer enameloid layer reaching maximum thickness early in development [21]. The cross-section of a saw blade is either wedge shaped or hollow ground, but a shark tooth is a convex structure.…”
Section: Discussionmentioning
confidence: 99%